Green natural nail polish modified with essential oils to treat onychomycosis. Issue 12 (31st July 2022) - Di Vito, Maura; Scafuro, Claudia; Mariotti, Melinda; Garzoli, Stefania; Torelli, Riccardo; Zhiri, Abdesselam; Sanguinetti, Maurizio; Bugli, Francesca
Abstract: Background: Onychomycosis (OM) accounts for about 50% of nail disorders in industrialised countries. Essential oils (EOs), aromatic natural compounds, are known for their antimicrobial activity. Objective: The aim of this work was to evaluate the antifungal efficacy of seven EOs and a commercial MIX against 10 dermatophytes responsible for OM to select the most effective ones to be included in a preventive or curative formulation based on a green natural nail polish (GNNP). Methods: Micro‐broth dilution tests in line with EUCAST guidelines and olfactory satisfaction test were performed to select the best natural compounds previously analysed by SPME coupled with GC‐MS. The same method was used to evaluate the release over time of the active compounds present in the two modified‐GNNPs made by adding the best natural compound selected (the C. citratus EO) and the MIX. Furthermore, to evaluate the preventive and curative activity of modified‐GNNPs, ex vivo experiments on healthy or colonised nails were performed. Results and Conclusions: Data showed that MIX‐modified‐GNNP had preventive activity as it inhibits the fungal growth by releasing its active ingredients for 7 days, while the OE‐modified GNNP acts as a natural drug showing cytocidal activity on nails colonised by dermatophytes, but it requires two weekly applications.